Mechanical Deformation Accelerates Protein Ageing. Issue 33 (19th May 2017) - Valle‐Orero, Jessica; Rivas‐Pardo, Jaime Andrés; Tapia‐Rojo, Rafael; Popa, Ionel; Echelman, Daniel J.; Haldar, Shubhasis; Fernández, Julio M.
Abstract: A hallmark of tissue ageing is the irreversible oxidative modification of its proteins. We show that single proteins, kept unfolded and extended by a mechanical force, undergo accelerated ageing in times scales of minutes to days. A protein forced to be continuously unfolded completely loses its ability to contract by folding, becoming a labile polymer. Ageing rates vary among different proteins, but in all cases they lose their mechanical integrity. Random oxidative modification of cryptic side chains exposed by mechanical unfolding can be slowed by the addition of antioxidants such as ascorbic acid, or accelerated by oxidants. By contrast, proteins kept in the folded state and probed over week‐long experiments show greatly reduced rates of ageing. We demonstrate a novel approach whereby protein ageing can be greatly accelerated: the constant unfolding of a protein for hours to days is equivalent to decades of exposure to free radicals under physiological conditions. Abstract : Time will tell : Accelerated ageing occurs when a protein is held unfolded under force for long periods of time. Maintaining a protein extended for more than 20 h blocks its ability to refold. This loss of folding contraction is triggered by the exposure of cryptic side chains to the oxidative environment, and can be greatly slowed by antioxidants. This kind of oxidative damage is a hallmark of the loss of tissue elasticity that occurs during ageing.